2021
DOI: 10.1007/s10067-021-05874-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness and drug survival of golimumab in patients affected by psoriatic arthritis with cutaneous involvement

Abstract: Objectives To determine the effectiveness of golimumab (GLM) in improving joint, periarticular structures and cutaneous manifestations in patients with moderate to severe psoriatic arthritis (PsA) with cutaneous psoriasis in different real-life clinical settings and 48-month drug survival. Methods Clinical and laboratory records were collected from PsA patients treated with GLM at baseline (T0) and after 6, 12, 24, 36, and 48 months of treatment. Compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A Spanish study demonstrated comorbidities increase drug discontinuation in PsA and other SpA (32). Another study revealed a significant association between first bDMARD discontinuation and any metabolic comorbidity (46); contrasting results have been reported (47,48). Notably, a higher Charlson comorbidity index (CCI) appeared to be associated with poorer bDMARD adherence, as reported elsewhere (32,40).…”
Section: Original Papermentioning
confidence: 90%
“…A Spanish study demonstrated comorbidities increase drug discontinuation in PsA and other SpA (32). Another study revealed a significant association between first bDMARD discontinuation and any metabolic comorbidity (46); contrasting results have been reported (47,48). Notably, a higher Charlson comorbidity index (CCI) appeared to be associated with poorer bDMARD adherence, as reported elsewhere (32,40).…”
Section: Original Papermentioning
confidence: 90%
“…The 7‐year retention rate was 39.5% in a previous analysis of the registry (Pombo‐Suarez et al., 2021); 14 the rate in the current analysis was similar, at 37.7%, and remained the same at year 8. Different studies have reported 3‐, 4‐, or 5‐year retention rates for golimumab ranging from 35% to 65% (Aaltonen et al., 2017; Alegre‐Sancho et al., 2021; Chimenti et al., 2022; Michelsen et al., 2020; Serrano_Benavente et al., 2022; Thomas et al., 2018), and a systematic review reported 3‐year golimumab retention rates of 32%–67% (Svedbom, Storck et al., 2017). To the best of our knowledge, the current analysis is the first to report on the golimumab retention rate during 8 years of follow‐up in routine clinical practice in Spain.…”
Section: Discussionmentioning
confidence: 99%